2020
DOI: 10.1021/acsami.0c07186
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Low Program Current Memory Based on Self-Assembled All-Inorganic Perovskite Single Crystals

Abstract: Memory devices based on lead halide perovskite have attracted great interests because of their unique current− voltage hysteresis. However, current memory devices based on polycrystalline perovskites usually suffer from large intrinsic electronic current and parasitic leakage current due to the existence of grain boundaries, which further leads to high power consumption. Here, a low-power resistance switching randomaccess memory device is demonstrated by assembling singlecrystalline CsPbBr 3 on Ag electrodes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Given its excellent scalability, simple structure, high-endurance cycles, fast operation, and high-density data storage, RRAM is considered an ideal candidate to meet the demands for the promising non-volatile memory of the future. Regarding its application in information capacity, however, there are a variety of issues that need to be addressed, such as retention characteristics, fatigue, and transmission mechanisms [10,11]. In general, one of the most significant advantages of a typical RRAM lies in its simple metal-insulator-metal (MIM) device structure, in which resistive switching (RS) layers are sandwiched between two metal electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Given its excellent scalability, simple structure, high-endurance cycles, fast operation, and high-density data storage, RRAM is considered an ideal candidate to meet the demands for the promising non-volatile memory of the future. Regarding its application in information capacity, however, there are a variety of issues that need to be addressed, such as retention characteristics, fatigue, and transmission mechanisms [10,11]. In general, one of the most significant advantages of a typical RRAM lies in its simple metal-insulator-metal (MIM) device structure, in which resistive switching (RS) layers are sandwiched between two metal electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, when MHPs are illuminated, all-optical conversion occurs, as shown in Figure 2f. Under an overloaded external bias and illumination, the ions in the perovskite (I − , Br − , Pb 2+ , MA + ) [74][75][76][77] and electrode (Ag + ) [78,79] migrate out of the ABX 3 perovskite structure, resulting in defect band levels, as shown in Figure 2g, and the resistance changes subsequently. The ions can rapidly migrate in the MHPs as vacancies or interstitials due to low required activation energies, such as 0.1-0.6 eV for I − ion, [75,[80][81][82][83] which are responsible for the low electric field RS through filament formation and annihilation.…”
Section: Intrinsic Properties Of Mhps For Detecting and Sensingmentioning
confidence: 99%
“…Ion migration can only occur when the switching voltage is greater than the SET or RESET threshold voltage. [74,75,79] When a bias voltage of less than 0.5 V is applied, the ions did not migrate from the CsFAMA ternary perovskite devices, as shown in Figure 2h. [44] Here, the photocurrent could be calculated by the formula…”
Section: Intrinsic Properties Of Mhps For Detecting and Sensingmentioning
confidence: 99%
“…Ag → Ag + +e – ). Subsequently, the oxidized metal is reduced by electrons from the cathode to forms a cone-shaped metal filament (e.g., Ag + + e – → Ag). It has also been reported that the general RESET process is caused by halide vacancies or metal ruptures of the vertexes of cone-shaped filaments based on bias in the opposite direction of the SET bias. These mechanisms have been described using X-ray diffraction (XRD), , time-of-flight secondary ion mass spectroscopy, Kelvin probe force microscopy, conducting atomic force microscopy (c-AFM), and transmission electron microscopy …”
Section: Introductionmentioning
confidence: 99%
“…19−21 It has also been reported that the general RESET process is caused by halide vacancies or metal ruptures of the vertexes of coneshaped filaments based on bias in the opposite direction of the SET bias. 16−21 These mechanisms have been described using X-ray diffraction (XRD), 17,22 time-of-flight secondary ion mass spectroscopy, 20 Kelvin probe force microscopy, 23 conducting atomic force microscopy (c-AFM), 16 and transmission electron microscopy. 24 To improve the performance and stability of OHP devices, numerous studies on controlling the morphology and defects of OHP thin films for resistive memory devices have been conducted systematically.…”
Section: ■ Introductionmentioning
confidence: 99%